Description and Preliminary Evaluation of a Low-Cost Simulator for Training and Evaluation of Flexible Endoscopic Skills. (April 2016) - Berger-Richardson, David; Kurashima, Yo; von Renteln, Daniel; Kaneva, Pepa; Feldman, Liane S.; Fried, Gerald M.; Vassiliou, Melina C.
Background . The Society of American Gastrointestinal and Endoscopic Surgeons developed the Fundamentals of Endoscopic Surgery (FES) to test the knowledge and skills required to perform flexible endoscopy. The program includes online didactic material to complement the written component, but does not have a practice component for the skills portion. The purpose of this study was to develop and pilot test low-cost models to train for the hands-on component of the FES examination. Methods . Based on the deconstructed skills tested in FES, a low-cost simulator and metrics that model retroflexion, instrumentation and targeting, loop reduction, and mucosal evaluation were developed. The model is reuseable and requires a real endoscope and tower. Validity evidence was obtained by comparing performance between novice endoscopists (NEs) and experienced endoscopists (EEs). Results . Six NEs and 6 EEs participated. In retroflexion, EEs and NEs scored (median [interquartile range]) 72.9 (67.1; 78.6) and 37.9 (25.7; 50.0; P = .004), respectively. In targeting, EEs scored 102.0 (75.0; 110.0) and NEs scored 50.0 (25.0; 50.0; P = .089). In navigation and loop reduction, EEs scored 189.0 (108.0; 267.0) and NEs scored 0.0 (0.0; 0.0; P = .004). In mucosal evaluation, EEs scored 133.3 (103.3; 150.0) and NEs scored 66.7 (50.0; 103.3; P = .015). The median global scores were 116.6 (109.6; 135.8) for EEs and 39.1 (29.1; 40.6; P = .004) for NEs. Conclusion . This pilot study provides preliminary validity evidence to support using these tasks to measure basic flexible endoscopic skills. Subsequent studies will examine the implementation of a proficiency curriculum using this model and its value as a training tool for flexible endoscopy, or to prepare for the FES exam.